Revealing the impact of different precursors and solvents for supramolecular complex formation and in-situ C-doping in g-C3N4 with enhanced photocatalytic H2O2 production - Nordin, Nurul Atikah; Mohamed, Mohamad Azuwa; Mastuli, Mohd Sufri; Mohd Yusoff, Siti Fairus; Sugiura, Takashi; Manseki, Kazuhiro (Journal of industrial and engineering chemistry (Seoul, Korea), 2024)
The reinforced light-harvesting capability suppresses photocarrier recombination and increases the specificsurface area, representing the possibility of excellent photocatalytic performance for graphitic carbon nitride(CN) photocatalysts. Herein, the remarkable photocatalytic properties of porous carbon-doped g-C3N4 (CCN)were enhanced through the incorporation of a supramolecular complex, M-CA-U (melamine-cyanuric acid-urea),in DMSO as the carbon dopant source. Through the diverse characterization methods, the successful formation ofthe supramolecular g-C3N4 using varying polarity of solvent was verified, achieved through a simple hydrothermal/solvothermal process. The CCN-MCAU-DMSO photocatalyst achieved the maximum photocatalyticH2O2 production rate, 1.3-fold higher than other prepared samples. The outstanding performances of CCNMCAU-DMSO were probably attributed to the extended specific surface area, robust visible light response,adjusted electronic band structure, accelerated charge separation, and limited charge recombination. Thephotocurrent response and photoluminescence spectroscopy analysis confirmed excellent charge carriers andseparation. Overall, this work provided a new idea to design and construct high-efficiency porous supramolecularassembly of CCN photocatalysts for photocatalytic studies. KCI Citation Count: 0